The perceptions of older nurses regarding continuing to work in a nursing career after retirement: A qualitative study in two Chinese hospitals of different levels. (May 2020) - Li, Huanhuan; Sun, Dan; Wan, Zhenzhen; Chen, Jialu; Sun, Jiao
Abstract: Background: There is a shortage of nurses worldwide, and a large number of older nurses will be entering retirement in the near future. Older nurses have rich nursing experience, and their retirement is a major loss of resources for the nursing profession. Returning to work after retirement is becoming increasingly popular among retirees today, but there is limited knowledge of the perceptions of older nurses regarding continuing to work in a nursing career after retirement. Objectives: To explore older nurses' perceptions of continuing to work in a nursing career after retirement. Design and settings: We conducted a descriptive, qualitative study of older nurses from two public hospitals of different levels in China in 2018. Participants: A total of 27 older nurses aged 50–60 years were recruited, 15 from a tertiary hospital and 12 from a secondary hospital. Methods: Individual semi-structured interviews were conducted with older nurses. An interview guide was developed to explore nurses' perceptions of continuing to work in a nursing career after retirement. Thematic analysis was used for the data analysis. We developed an interview guide and analysed the data based on the three essential conditions of the framework for understanding behaviour. Findings: Based on the definition of the three essential conditions of the framework for understanding behaviour, 14 subthemes emerged from the data were categorised under this framework. The three main themes were as follows: the nurses' perceptions of their capability, motivation, and opportunity related to engaging in a nursing career after retirement. A number of older nurses with rich clinical experience have the ability and motivation to engage in nursing a career after retirement. However, discrimination against nurses, burnout, and the effects on young people's employment are barriers to older nurses considering working in a nursing career after retirement. Regarding re-employment after retirement, older nurses also expressed concerns about their physical health, family responsibilities, and salary as well as lack of managerial and policy support. Conclusions: These themes confirmed previous findings and offered new perspectives on older Chinese nurses' perceptions of working in a nursing career after retirement. These findings will influence future policy development and research directions. Policies for facilitating a prolonged working life should be developed. Future research should focus on how to address the challenges confronted by older nurses.